2017
DOI: 10.1002/hed.25053
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biofilm growth on modern voice prostheses

Abstract: The use of silver oxide and Teflon as valve flap materials proves to reduce long-term biofilm formation in vitro. The applied model allows rapid screening for novel biofilm-inhibitive materials and durable coatings designated for more biofilm resistant medical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As reported in [ 16 , 35 ], the esophageal surfaces of the investigated prosthesis–the esophageal flange, the valve flap, and the valve seating–were mostly covered by biofilm infestation. There were similar structures, like stiff and compact bulges in the biofilm layers, on the flanges described in previous studies [ 36 , 37 , 38 , 39 ] as we observed in our setting.…”
Section: Discussionmentioning
confidence: 63%
“…As reported in [ 16 , 35 ], the esophageal surfaces of the investigated prosthesis–the esophageal flange, the valve flap, and the valve seating–were mostly covered by biofilm infestation. There were similar structures, like stiff and compact bulges in the biofilm layers, on the flanges described in previous studies [ 36 , 37 , 38 , 39 ] as we observed in our setting.…”
Section: Discussionmentioning
confidence: 63%
“…Four different culture media commonly used in yeast biofilm studies (Lackey et al, 2013;Pereira et al, 2015;Tan et al, 2016;Tan et al, 2017;Leonhard et al, 2018;Goḿez-Molero et al, 2021) were selected and ranked in terms of nutritional content, from highest to lowest: 1) YPD, a complex medium that supports yeast growth without selective conditions (Tan et al, 2016). It contains yeast extract and peptone that stimulate fungal replication.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…An in vitro study on biofilm growth was conducted on various choices of the modern TEP voice prostheses, which concluded that use of silver oxide coating and Teflon as valve flap materials showed significantly less surface biofilm formation. 17 It might more effectively protect users against the current pandemic, since viral particles could penetrate the exopolymeric matrix of mucoid biofilms and thus benefit from a protective environment against external aggressions. 18 A dedicated brush should be used during cleansing of an indwelling device while facing a mirror to prevent colonization of pathogens with drinking water.…”
Section: Voice Rehabilitation Devicesmentioning
confidence: 99%
“…TEP voice prostheses could be indwelling or nonindwelling and made with different materials. An in vitro study on biofilm growth was conducted on various choices of the modern TEP voice prostheses, which concluded that use of silver oxide coating and Teflon as valve flap materials showed significantly less surface biofilm formation 17 . It might more effectively protect users against the current pandemic, since viral particles could penetrate the exopolymeric matrix of mucoid biofilms and thus benefit from a protective environment against external aggressions 18 .…”
Section: Protocol For Care Of Laryngectomy Stoma In Covid‐19mentioning
confidence: 99%